Mountain woman [large type] : how she defied the odds in the time of the mountain men, a novel - Lalire, Gregory (Thorndike Press large print softcover western, 2023)
"The early 19th-century trappers who traipse through the Rockies in search of beaver pelts are called mountain men-all but one, whose unique tale is told here by her daughter, Bathsheba Hex, in 1901. In 1819, Kentucky-born Bet Hex ventures up the Missouri River with a fur-trading expedition. Captured first by Arapahos and then by Pawnees, she is rescued by a French voyageur. After his death, she sets out alone to make her home in the wilderness. The Blackfeet call her "White Woman Who Never Dies" and she lives up to that name, surviving wildfires, harsh winters, and the dangers of both animal and human predators. In the Bitterroot Mountains she befriends a Salish man, raises a little girl, and deals with Blackfeet raiders and Black Robe missionaries. While she would rather swim with the beavers than kill them and rather love a man than fight him, Bet Hex does what she must to survive as the one and only mountain woman"--